Idle Youth in Mexico : Trapped between the War on Drugs and Economic Crisis - de Hoyos, Rafael; Gutierrez Fierros, Carlos; Vargas M., J. Vicente (World Bank, Washington, DC, 2016)
The present study combines data from Mexico's employment surveys (Encuesta Nacional de Empleo and Encuesta Nacional de Ocupación y Empleo) with the country's official statistics on murder rates to create a state-level panel data set covering the period 1995 to 2013. Including most of the common controls identified by the literature, the results show that the rate of male youth ages 19 to 24 not studying and out of work (the so-called ninis), is not correlated with homicide rates during the period 1995 to 2006. However, there is evidence that a positive correlation between male ninis and murder rates arises between 2007 and 2013, a period during which murder rates in Mexico increased threefold. The association between ninis and homicide rates is stronger in states located along the border with the United States, a region particularly affected by organized crime and the international financial crisis of 2008-09.